(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines contemporary psychological concepts - the dark and light triads of personality. The dark triad encompasses negative personality traits such as narcissism, Machiavellianism, and psychopathy, while the light triad comprises positive traits like altruism, empathy, and humanity. The article explores how this model enables understanding of individual behavior through sources of motivation and social orientation of the personality.